Improving ESP Writing Class Learning Outcomes Among Medical University Undergraduates: How Do Emotions Impact? - Hu, Nan; Chen, Min (Frontiers in Psychology, 2022)
As English plays a significant role in most professions, improving the English for Specific Purpose (ESP) writing competence allows individuals to participate in the global professional community, which makes ESP writing important for research. However, research on ESP writing is reported to be insufficient, and how factors such as emotions affect ESP writing is rarely and marginally studied. Therefore, this study aimed at investigating how induced emotions influence the learning outcome in ESP writing classes with an emphasis on a particular rhetorical choice among medical university undergraduates. A total of 63 medical university undergraduates were recruited. After the emotional inducement, they were taught with materials selected and adopted from the BioCauses corpus and with an explicitly inductive teaching approach. Results revealed that positive emotions positively correlated with better learning outcomes, while negative emotions hindered participants in their learning. The results shed light on the impact of emotional states on ESP/medical research article (MRA) writing, learning, and teaching. Further study implications were provided accordingly.